240 likes | 331 Views
Chapter 6. Section 6.1. Exercise #9. Determine which of the ordered pairs are solutions for the given equation. 3x 2y = 12. (0, 6),. (4, 0),. 3(4) 2(0) = 12. 12 0 = 12. true. (4, 0). 3( ) 2( 5 ) = 12. (4, 0).
E N D
Chapter 6 Section 6.1 Exercise #9
Determine which of the ordered pairs are solutions for the given equation. 3x 2y = 12 (0, 6), (4, 0), 3(4) 2(0) = 12 12 0 = 12 true (4, 0)
3( ) 2(5) = 12 (4, 0) Determine which of the ordered pairs are solutions for the given equation. 3x 2y = 12 (0, 6), (4, 0), 2 (10) = 12 true
(4, 0) Determine which of the ordered pairs are solutions for the given equation. 3x 2y = 12 (0, 6), (4, 0), 3(0) 2(6) = 12 0 12 = 12 Not true
3( 5) 2() = 12 (4, 0) Determine which of the ordered pairs are solutions for the given equation. 3x 2y = 12 (0, 6), (4, 0), 15 (3) = 12 true
Chapter 6 Section 6.1 Exercise #21
Complete the ordered pairs so that each is a solution for the given equation. 3x 2y = 12 (2, ), ( , 0), ( , 3 ) 4 ( , 6), 3x 2(0) = 12 3x 0 = 12 3x = 12 x = 4
Complete the ordered pairs so that each is a solution for the given equation. 3x 2y = 12 (2, ), 4 ( , 0), ( , 3 ) 0 ( , 6), 3(x) 2(6) = 12 3(x) + 12 = 12 3x = 0 x = 0
Complete the ordered pairs so that each is a solution for the given equation. 3x 2y = 12 (2, ), ( , 0), ( , 3 ) 4 0 ( , 6), 3 3(2) 2y = 12 6 2y = 12 2y = 6 y = 3
Complete the ordered pairs so that each is a solution for the given equation. 3x 2y = 12 (2, ), ( , 0), ( , 3 ) 6 4 0 ( , 6), 3 3x 2(3) = 12 3x 6 = 12 3x = 18 x = 6
Chapter 6 Section 6.1 Exercise #23
( , ) ( , ) –9 x = 3 Complete the ordered pairs so that each is a solution for the given equation. y = 3x + 9 ( , 0) (0, ) 3 0 = 3x + 9 –9 = 3x x = 3
( , ) ( , ) y = 3 ( ) + 9 Complete the ordered pairs so that each is a solution for the given equation. y = 3x + 9 ( , 0) (0, ) 11 3 y = 2 + 9 y = 11
( , ) ( , ) Complete the ordered pairs so that each is a solution for the given equation. y = 3x + 9 ( , 0) (0, ) 9 11 3 y = 3(0) + 9 y = 9
( , ) ( , ) y = 3 ( ) + 9 – Complete the ordered pairs so that each is a solution for the given equation. y = 3x + 9 ( , 0) (0, ) 9 7 11 3 y = – 2 + 9 y = 7
Chapter 6 Section 6.1 Exercise #27
Find four solutions for the following equation. x y = 7 Solution with x = 0: 0 y = 7 y = 7 y = 7 (0, 7)
Find four solutions for the following equation. x y = 7 Solution with x = 2: 2 y = 7 y = 5 y = 5 (0, 7) (2, 5)
Find four solutions for the following equation. x y = 7 Solution with x = 4: 4 y = 7 y = 3 y = 3 (0, 7) (2, 5) (4, 3)
Find four solutions for the following equation. x y = 7 Solution with x = 6: 6 y = 7 y = 1 y = 1 (0, 7) (2, 5) (4, 3) (6, 1)
Chapter 6 Section 6.1 Exercise #43
An equation in three variables has an ordered triple as a solution. For example, (1, 2, 2) is a solution to the equation x + 2y – z = 3. Complete the ordered-triple solution for the following equation. 2x + y + z = 2 (–2, , 1) 5 2(–2) + y + (1) = 2 –4 + y + (1) = 2 –3 + y = 2 y = 5
Chapter 6 Section 6.1 Exercise #49
x 1 2 3 6 4 y Statistics. The number of programs for the disabled in the United States from 1993 to 1997 is approximated by the equation y = 162x + 4365 in which x is the number of years after 1993. Complete the following table. 4527 4689 4851 5013 5337